If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2sinx + 3cosx = 4x Reorder the terms: 3cosx + 2insx = 4x Solving 3cosx + 2insx = 4x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2insx' to each side of the equation. 3cosx + 2insx + -2insx = -2insx + 4x Combine like terms: 2insx + -2insx = 0 3cosx + 0 = -2insx + 4x 3cosx = -2insx + 4x Divide each side by '3osx'. c = -0.6666666667ino-1 + 1.333333333o-1s-1 Simplifying c = -0.6666666667ino-1 + 1.333333333o-1s-1
| 9h=7h | | 6x+10=64-3x | | 0=4x^3-12x^2-24x+32 | | .04x^2-4x=0 | | 2[5+2(9-4)]= | | 12+8x=4x+20 | | 9u+4+8t+3u= | | 5-2x+2=15 | | 2y=6-2.5x | | 9xsquared+16x=41 | | 9x+2=-5 | | 3x^2-12x-5=-6x^2 | | 6=2y+2.5x | | 6=2.5x+2y | | -9x+2=5 | | 5=3x-2+4x+1 | | 8x-(22x+7)=5x(2x-2)+8 | | 7x+5y-5(4x-7y)= | | B=(r+k)f | | y=15-10 | | 9y-8y-3=7 | | -81=5x-2(-2x+9) | | 3p^5=12 | | 2x^2-7x-1=3 | | 2(-4+3y)+6y=5 | | 2x+14+12y= | | x+(x*.15)=40 | | (x+7)+9=0 | | 9(z+1)-4(z-4)=2(z-1)+2(z-3) | | -3.3y=-23.1 | | 2x+14+22y= | | 14=18-4c |